Analysis of Activator and Consequences with Safe Behaviors - Resky Sabaniah Jaya (Journal of Aafiyah Health Research (JAHR), 2022)
Backgrounds: Unsafe behavior of workers in hospitals when working without using personal protective equipment according to standards can result in work accidents and cause work-related diseases. The recorded work accidents are in 2019 nurses who were exposed to B3 fluids and in 2020 there were also Nurses with needle sticks who have a higher number of work accidents if safe behavior is not carried out in hospitals. This study aims to analyze the activator and consequences with Safe Behavior on Workers at the Lamaddukkelleng Sengkang Regional General Hospital, Wajo Regency. Methods:The type of research used in this study is Analytical Observational which is a Cross-Sectional Study. The population in this study is patients who make repeated visits as many as 722 patients with the number of samples in this study, namely 88 patients drawn by purposive sampling method. This research was processed using the SPSS computerized program. The data analysis used is univariate, bivariate, and multivariate analysis. Results: There is an effect of knowledge with a significance value of 0.006, there is an influence of supervision with a significance value of 0.007, there is an effect of training with a significance value of 0.015, there is an effect of awareness with a value of p = 0.000, there is an effect of personal protective equipment with a significance value of 0.001, there is an effect of reward with a value of 0.037 significance for safe behavior, there is no effect between punishment with a significance value of 0.065 on safe behavior. Conclusions: There is an influence between knowledge, supervision, training, awareness, personal protective equipment, rewards and there is no effect between punishment on workers' safe behavior. Researchers suggest always paying attention to factors related to safe behavior.